Poster 249: Distal Femoral Coronal Realignment Osteotomies Alter CT-Measured Tibial Tuberosity to Trochlear Groove (TT-TG) Distance in Addition to Mechanical Axis Deviation – A Cadaveric Study - Tauberg, Brandon M.; Williams, Derrick; Aboulafia, Alexis H.; Haidar, Layla; Mansour, Alfred A. (Orthopaedic journal of sports medicine, 2024)
Objectives: Patellar tracking has been shown to be affected by limb alignment. Many patients with underlying valgus deformity with patellar instability have elevated tibial tuberosity–trochlear groove (TT-TG) measurements. Correction of limb alignment improves Q-angle, however, its effect on TT-TG as measured by computed tomography (CT) has yet to be demonstrated. We hypothesize that changing the limb alignment as measured by mechanical axis deviation (MAD) through a distal femoral osteotomy (DFO) would also cause a change in TT-TG distance as measured by CT. Methods: Lateral distal femoral osteotomies were performed on 5 cadaveric specimens (10 limbs) and fixed with an external fixator. The native MAD and baseline TT-TG were measured using a CT scanogram. Subsequent scans were then performed altering the MAD using calibrated radiolucent wedges in 5 mm increments (0-25 mm) on a single side, using the contralateral limb as the control. Repeat measurements of MAD and TT-TG were obtained, and once completed, original alignment was restored, and the contralateral limb was taken through the same protocol with the opposite limb serving as the control. Measurements were performed by two independent observers and averages obtained. Linear regression models were created, and statistical analysis of variance was performed. Results: A CT-scanogram that measured TT-TG distances were significantly altered by changes in limb alignment. According to our linear regression model, each 1° of MAD alteration resulted in TT-TG change of approximately 0.4 mm. With every 5° change in limb alignment, the TT-TG changed by approximately 2 mm (Figure 1). Altering MAD from 6° valgus to 7° varus decreased the TT-TG mean from 14.3 mm to 7.7 mm, p < 0.05. Conclusions: Changes in coronal limb alignment through a distal femoral corrective osteotomy produce significant changes in TT-TG in addition to correcting MAD in a cadaveric model. These findings should be considered when determining appropriate corrective procedures for patients with valgus alignment and patellar instability. Figure 1